2001
DOI: 10.1902/jop.2001.72.6.741
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Infection in Cyclosporin‐Induced Gingival Overgrowth in Renal Allograft Recipients

Abstract: The suppression of T-cell function by cyclosporin therapy can result in an increase of HPV infection, adding to the proliferative activity of cyclosporin in the oral mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
14

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 15 publications
0
12
0
14
Order By: Relevance
“…20 Other researchers, using the Southern blot method with 32P-radiolabeled DNA found HPV in 30% of gingival tissue with gingivitis or periodontitis, which also suggested gingival epithelium was a potential reservoir for HPV; 34 and 92.3% of 13 biopsies of gingival overgrowth lesions in renal allograft recipients were HPV +. 17 …”
Section: Discussionmentioning
confidence: 99%
“…20 Other researchers, using the Southern blot method with 32P-radiolabeled DNA found HPV in 30% of gingival tissue with gingivitis or periodontitis, which also suggested gingival epithelium was a potential reservoir for HPV; 34 and 92.3% of 13 biopsies of gingival overgrowth lesions in renal allograft recipients were HPV +. 17 …”
Section: Discussionmentioning
confidence: 99%
“…In patients with acute myeloid leukemia, HSV may be an important pathogen of oral mucosal ulcerations (214). Viruses other than herpesviruses can also reside in the human periodontium, but their relationship to destructive periodontal diseases remains unclear (18, 30, 65, 116, 140, 143, 144, 176, 199, 250). Hormia et al.…”
Section: Herpesviruses In Periodontal Diseasementioning
confidence: 99%
“…Ciclosporin was used as a local immunosuppressant in this patient, and it is postulated that this immunosuppressive therapy lead to the reactivation of the virus in this patient. 10 Seibel et al 11 demonstrated the development of similar lesions in dogs treated with ciclosporin. 6 This complex of ciclosporin and cyclophilin inhibits calcineurin, an enzyme which under normal circumstances is responsible for activating the transcription of interleukin-2 and the resulting T-cell clonal expansion.…”
Section: Discussionmentioning
confidence: 98%